ANALISIS BENTUK GERAK TARI HADRAH DI SANGGAR JAYA RAYA KOTA RANAI KABUPATEN NATUNA KEPULAUAN RIAU - Fitri, Rosa Elisa; Ismunandar, Ismunandar; Aditya, Mega Cantik Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to provide a comprehensive description and analysis of the Hadrah dance movement in Sanggar Jaya Raya, Ranai, Natuna Regency, Riau archipelago using textual information, photos, and videos. The issue arises from the manner in which the movements and components of the Hadrah dance are executed in Sanggar Jaya Raya in Ranai. This study employs the descriptive qualitative method, in addition to utilizing semiotic and ethnochoreological methodologies. The methods employed for data collection are observation, interviews, and documentation. Extended observation and triangulation are methods used to evaluate the accuracy of data. According to the data analysis, it can be inferred that the Hadrah dance style in Sanggar Jaya serves as a hospitable dance for esteemed guests or as an introductory dance during an event. Sanggar Jaya Raya offers a Hadrah dance variation that comprises an initial greeting movement, followed by a sequence of "bunga silet ukel" movements leading to "bercocok tanam" movements, and concludes with a closing greeting movement. This dance showcases an equal number of female and male dancers, with both even and odd numbers. The floor features a horizontal pattern. The researcher anticipates that the results of this study will be highly beneficial to readers, offering profound insights into the analysis of the Hadrah dance movement, and serving as a reliable and precise reference.